The Effectiveness of Local Level Government-Facilitated Mediation in Conflict Resolution (The Journal of Nuwakot Adarsha Multiple Campus, 2025)
This study investigate the efficacy of mediation facilitated by local governments in resolving conflicts in Nepal. As an alternative dispute resolution mechanism, mediation has gained significance within Nepal's legal framework, particularly with the Local Government Operation Act empowering judicial committees to mediate community disputes. Nonetheless, there is a paucity of empirical evidence on the effectiveness of these mediation processes. This study seeks to evaluate the procedural effectiveness and community impact of local government-facilitated mediation, identify factors influencing mediation outcomes, examine stakeholder perceptions, and propose policy recommendations to enhance mediation frameworks. This study employed a mixed methods approach that integrates quantitative and qualitative data collection and analysis. Purposive sampling was utilized to select municipalities with operational judicial committees, ensuring diversity in geographic, ethnic, gender, and caste representation. This study acknowledges limitations related to sampling, accessibility, response bias, and the complexity of legal and institutional frameworks. The anticipated outcomes include contributions to the academic discourse on informal justice systems and practical recommendations for improving mediation practices, promoting inclusivity, and enhancing access to justice. The findings aim to support policy reforms and institutional strengthening, rendering mediation a more effective and sustainable tool for dispute resolution within Nepal's evolving governance system